A PCR-free screen-printed magnetic electrode for the detection of circular RNA from hepatocellular cancer based on a back-splice junction. Issue 29 (17th May 2021) - Zhang, Bin; Liang, Yitao; Bo, Liang; Chen, Mingyu; Huang, Bobo; Cao, Qingpeng; Wei, Jinwei; Li, Tianyu; Cai, Xiujun; Ye, Xuesong
Abstract : Functional magnetic beads with capture probes based on specific back-splice junction sites were employed to identify and selectively isolate target circRNA. Abstract : Circular RNA (circRNA) has the potential to be applied to disease diagnosis and therapy. However, the currently available circRNA detection techniques are limited. This work proposes a sensitive and selective approach for circRNA detection based on gold nanoparticle-modified screen-printed magnetic electrodes (AuNPs-SPME). Magnetic beads (MBs) with capture probes based on specific back-splice junction (BSJ) sites were employed to identify and selectively isolate the target circRNA, which could be directly adsorbed onto the AuNPs-SPME. Then, the circRNA attached to the surface was detected by changes in the methylene blue redox signal. The simple and time-saving AuNPs-SPME is highly sensitive (LOD = 1.0 pM) to circCDYL, one of the biomarkers of hepatocellular cancer (HCC). The analytical performance of the method presented has also been verified in human serum samples, holding great promise for clinical diagnosis.